Effects of Standardized Ileal Digestible Lysine:Crude Protein Ratio on Growth Performance of 25- to 55-lb Pigs - Jessica L. Smallfield; Jordan T. Gebhardt; Katelyn N. Gaffield; Mike D. Tokach; Jason C. Woodworth; Robert D. Goodband; Joel M. DeRouchey; Dwight J. Shawk; Noah C. Gainey (Kansas Agricultural Experiment Station Research Reports, 2024)
A total of 4,167 pigs (initially 28.7 ± 0.59 lb) were used in a 21-d growth study to evaluate SID Lys:CP ratios for 25- to 55-lb pigs. Pigs were weaned at approximately 21 d of age and pens of pigs were randomly allotted to one of 10 dietary treatments in a randomized complete block design. Pens of pigs were blocked based on sow farm origin, date of entry into the facility, and average pen weight. A total of 160 pens were used with 80 double-sided, 5-hole stainless steel fence-line feeders, with feeder serving as the experimental unit. For each feeder, one pen contained approximately 26 gilts, and one pen contained approximately 26 barrows. There were eight replicates per dietary treatment. A pelleted phase 1 diet was fed to all pigs with 1.25 lb/pig budgeted, followed by a phase 2 diet fed in meal form until beginning of the experiment on d 21 post-weaning. Phase 3 experimental treatments were arranged in a 2 × 5 factorial with main effects of SID Lys (1.15 or 1.30%) and SID Lys:CP ratio (6.00, 6.22, 6.46, 6.72, and 7.00). From d 0 to 7 (period 1), there was a tendency for a SID Lys:CP × SID Lys interaction (quadratic, P = 0.077), where feed efficiency improved at 6.22 SID Lys:CP and worsened (quadratic, P = 0.001) as the ratio increased in diets formulated to 1.15% SID Lys, while feed efficiency worsened (linear, P = 0.010) as SID Lys:CP ratio increased in diets formulated to 1.30% SID Lys. As the SID Lys:CP ratio increased, ADG increased (quadratic, P = 0.043) up to 6.46 SID Lys:CP ratio, and then decreased as the ratio increased thereafter. As the SID Lys:CP ratio increased, ADFI increased (linear, P = 0.028). From d 7 to 14 (period 2), a SID Lys:CP × SID Lys interaction was observed (linear, P = 0.008) for F/G where increasing SID Lys:CP ratio worsened (linear, P < 0.0001) F/G in diets formulated to 1.15% SID Lys while no response was observed in diets formulated to 1.30% SID Lys. Additionally, as the SID Lys:CP ratio increased, ADFI increased (linear, P = 0.013). From d 0 to 14 (periods 1 and 2), a SID Lys:CP × SID Lys interaction was observed (linear, P = 0.0002) where increasing SID Lys:CP ratio worsened feed efficiency in both SID Lys levels, but the magnitude was greater in diets formulated to 1.15% SID Lys (quadratic, P = 0.016) compared to 1.30% SID Lys (linear, P = 0.0004). Increasing SID Lys:CP ratio increased (linear, P = 0.004) ADFI. From d 14 to 21 (period 3), as the SID Lys:CP ratio increased, feed efficiency worsened (linear, P = 0.004). From d 0 to 21 (overall), a SID Lys:CP × SID Lys interaction was observed (linear, P = 0.012) where increasing the SID Lys:CP ratio reduced (P < 0.0001) feed efficiency at both SID Lys levels, but the magnitude was greater in diets formulated to 1.15% SID Lys compared to 1.30% SID Lys. Additionally, ADFI increased (P = 0.013) as the SID Lys:CP ratio increased. Increasing SID Lys increased (P < 0.001) ADG in phases 1, 2, and overall, but not from d 14 to 21. In conclusion, increasing SID Lys:CP ratio worsened feed efficiency, especially when the ratio increased beyond 6.46. Data suggests that diets for 25- to 55-lb pigs should be formulated to a SID Lys:CP ratio of 6.46 or lower to maintain feed efficiency.
Keywords: crude protein; lysine; nursery pig; SID Lys:CP